2019
DOI: 10.3390/su11041178
|View full text |Cite
|
Sign up to set email alerts
|

A New Sustainable Model for Risk Management—RiMM

Abstract: All activities of a company involve risk. In order to achieve its objectives, an organization must identify, analyze, evaluate and then treat all significant risks. According to ISO international standards in the risk field, risk management can be applied to an entire organization, at its many areas and levels, at any time, as well as to specific functions, projects and activities. An effective risk management helps top management of an organization to make optimum decisions and to prevent losses. This paper p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…In terms of identifying potential risks, some studies also confirmed that ISO 31000:2018 was able to help the company identify the upcoming risks that it has to face (Mormul, 2021;Ruiz-Canela López, 2021). Since ISO 31000:2018 brings benefits to the company, this ERM is believed to be effective in reducing company losses (Ahn et al, 2020;Tiganoaia et al, 2019).…”
Section: Reduce Lossesmentioning
confidence: 94%
“…In terms of identifying potential risks, some studies also confirmed that ISO 31000:2018 was able to help the company identify the upcoming risks that it has to face (Mormul, 2021;Ruiz-Canela López, 2021). Since ISO 31000:2018 brings benefits to the company, this ERM is believed to be effective in reducing company losses (Ahn et al, 2020;Tiganoaia et al, 2019).…”
Section: Reduce Lossesmentioning
confidence: 94%
“…DRESS-eAI is designed to focus on the detection of pitfalls and enact the fundamentals relevant to most eAI use-cases while being structured as a process that is familiar to organizations as it is comparable to the International Organization for Standardization (ISO) standard 31000:2009 for risk management [30]. This is an accepted standard for risk management developed by hundreds of risk management professionals over the course of four years, and has previously seen utilisation within sustainability focused methodology [31]. The six process phases of the methodology are inspired directly by the IS0 31000:2009 risk management process with each phase being identified as a necessary step for systematically ensuring rigorous eAI practices of an organization.…”
Section: Proposal Of a Generalized Eai Risk Assessment Methodologymentioning
confidence: 99%
“…Manage risk and cost-related risk as well as environmental, technical, and market risk [48][49][50] Environmental risk, technology risk, management risk, and market risk [51,52] Technology risk, market risk, transportation capacity, competition risk, and policy risk [53,54] Risk characteristics Technology risk, management risk, and marketing risk [55,56] Technology risk, manufacturing risk, market risk, management risk, and financial risk [57,58] Technology risk, market risk, cooperative risk, financial risk, and institutional risk [59,60] Risk processes Development risk, manufacturing risk, and marketing risk [61,62] Research risk, manufacturing risk, and market service risk [63] Development risk, manufacturing risk, and market risk [64] The classification of the risk management process by the International Standards Association, American Project Management Organization, Australian And New Zealand Standards, and American Sponsor Committee is basically the same, including environmental analysis, risk identification, risk assessment, risk response, and risk internal control [65][66][67][68]. For identifying green innovation risk, the flowchart method, fault tree method, and scenario analysis method are usually used.…”
Section: Risk Sourcesmentioning
confidence: 99%
“…Many scholars summarized the research on the linear model of green innovation. The result of the research is that green innovation is a linear process of research, development, manufacturing, and marketing, and the chain model of green innovation is established [67]. The main chain is defined as potential market, research and production exploration, specific design and test, secondary design and production, market and service.…”
Section: Process Of Green Innovation Risk Identificationmentioning
confidence: 99%
See 1 more Smart Citation